2013
DOI: 10.6061/clinics/2013(sup01)12
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for sperm retrieval and sperm injection outcomes in obstructive azoospermia: Do etiology, retrieval techniques and gamete source play a role?

Abstract: Obstructive azoospermia is a relatively common male infertility condition. The main etiologies of obstructive azoospermia include congenital, surgical-derived, traumatic and post-infectious cases. Although seminal tract reconstruction is a cost-effective treatment in most cases, this approach may not be feasible or desired in some cases. In such cases, assisted reproduction techniques offer a method for achieving pregnancy, notably via sperm retrieval and intracytoplasmic sperm injection. This process requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 72 publications
(86 reference statements)
0
29
0
1
Order By: Relevance
“…Miyaoka R et al in their article published in 2013 mention pregnancy rates between 31% to 43% after using surgically retrieved sperms for ICSI. (12) Dabaja et al in his study published in 2013 found pregnancy rate of 48% by using retrieved sperms (25) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miyaoka R et al in their article published in 2013 mention pregnancy rates between 31% to 43% after using surgically retrieved sperms for ICSI. (12) Dabaja et al in his study published in 2013 found pregnancy rate of 48% by using retrieved sperms (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Once fertilized, the embryo is implanted into female uterus for development. (10,11) The sperm recovery rates ranges from 90% to 100% for obstructive azoospermia using any of standard surgical technique (12) , but the sperm recovery rates for non-obstructive azoospermia range from 30-63% for TESE, and 43-63% for Micro-TESE; the rate for TEFNA is approximately 47%. (17) Out of all patients of azoospermia approximately 36% are due to obstructive azoospermia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In OA both reconstructive procedures and surgical retrieval are highly successful. [6][7][8] Non-Obstructive azoospermia (NOA) is associated with a spectrum of various severe and untreatable conditions associated with an intrinsic testicular impairment. 9 Parameters like history, physical examination, testicular volume and hormonal analysis (FSH, LH, TSH, Testosterone) and even the histology of a diagnostic biopsy are only indicative and not always predictive in diagnosing the cause of azoospermia because patients with maturation arrest (MA) generally have welldeveloped and normal-sized testes and normal hormonal levels.…”
Section: Introductionmentioning
confidence: 99%
“…Среди всех видов азооспермий обструктивная фор-ма встречается в 40 % случаев и является наиболее благоприятной для исходов программ ВРТ [54]. В ме-таанализе, проведенном J. D. M. Nicopoullos и соавт.…”
unclassified